O insulă exotică a culturii române: Dora d’Istria - Liviu Bordaş (Revista de Istorie și Teorie Literară)
The article addresses a few key issues of the life and work of Dora d’Istria (1828–1888) in the context of an increasing interest for this Romanian writer of French expression. Among the recent publications, it highlights the first scientific monograph published by Antonio d’Alessandri, Il pensiero e l’opera di Dora d’Istria fra Oriente Europeo e Italia [“The thought and work of Dora d’Istria between Eastern Europe and Italy”], in the well-known collection of the “Istituto per la Storia del Risorgimento Italiano” (Gangemi Editore, Roma, 2007). The cosmopolitanism of Elena Ghica, as a personal option, is analysed against the background of her reception in her native country. In close connection with this, we attempted a first analysis of the Albanian origin myth, which played an important role in her intellectual activism after 1866. Finally, we evaluate the possibility of realising an edition/translation of her Complete Works in the present context and propose the solution of a digital library.